Stochastic Modeling of Manufacturing Systems Advances in Design, Performance Evaluation, and Control Issues - Liberopoulos, George; Papadopoulos, Chrissoleon T.; Tan, Barış; MacGregor Smith, James; Gershwin, Stanley B.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2006)
Manufacturing systems rarely perform exactly as expected and predicted. Unexpected events, such as order changes, equipment failures and product defects, affect the performance of the system and complicate decision-making. This volume is devoted to the development of analytical methods aiming at responding to variability in a way that limits its corrupting effects on system performance. The book includes fifteen novel chapters that mostly focus on the development and analysis of performance evaluation models of manufacturing systems using decomposition-based methods, Markovian and queuing analysis, simulation, and inventory control approaches. They are organized into four distinct sections to reflect their shared viewpoints: factory design, unreliable production lines, queuing network models, production planning and assembly.
Factory Design -- Dilemmas in factory design: paradox and paradigm -- Unreliable Production Lines -- Lean buffering in serial production lines with non-exponential machines -- Analysis of flow lines with Cox-2-distributed processing times and limited buffer capacity -- Performance evaluation of production lines with finite buffer capacity producing two different products -- Automated flow lines with shared buffer -- Integrated quality and quantity modeling of a production line -- Stochastic cyclic flow lines with blocking: Markovian models -- Queueing Network Models of Manufacturing Systems -- Performance analysis of multi-server tandem queues with finite buffers and blocking -- An analytical method for the performance evaluation of echelon kanban control systems -- Closed loop two-echelon repairable item systems -- A heuristic to control integrated multi-product multi-machine production-inventory systems with job shop routings and stochastic arrival, set-up and processing times -- Performance analysis of parallel identical machines with a generalized shortest queue arrival mechanism -- A review and comparison of hybrid and pull-type production control strategies -- Stochastic Production Planning and Assembly -- Planning order releases for an assembly system with random operation times -- A multiperiod stochastic production planning and sourcing problem with service level constraints.
Keywords: Production management; Operations research; Decision making; Engineering economics; Engineering economy; Operations Management; Operations Research/Decision Theory; Engineering Economics, Organization, Logistics, Marketing